TEAMWORK AS A COMPONENT OF SOCIAL COMPETENCE OF YOUNG SCIENTISTS - Tetiana Shkoda; Inna Semenets-Orlova; Volodymyr Kyryliuk (Baltic Journal of Economic Studies, 2022)
The research satisfies the current world trends in future jobs, where team work is considered as one of the significant soft skills till 2030. The purpose of the paper is to identify the key team roles, which have leading impact on social competence of young scientists in Ukraine. The novelty of the research is represented by the created theoretical model of social competence and its connection with team work. The proposed model includes such blocks as: approaches to definition, structural elements in combination with evaluation criteria, types of an individual’s social competence, functions and levels of social competence as well as approaches to social competence research. The object of the scientific research is the process of using team work tools in social competence management of young scientists’ teams. The research methodology includes such methods: comparative analysis, critical analysis, descriptive analysis, factor analysis, and cluster analysis. The research is based on the results of the special direction of the mass sociological survey of young scientists in Ukraine. The limitations of the research are that the period of gathering data covers 2020 year before the war in Ukraine. The Belbin’s approach to team roles was taken for researching the current state of team work as an important part of social competence of young scientists in Ukraine. The obtained results confirmed quite equal distribution of managers’ types in the teams of young scientists. The most important team roles are Implementer and Team-worker that corresponds to the young scientists’ basic functions. But, such team roles as Monitor-evaluator, Resource Investigator and Plant require better development. The practical value of the research for the young scientists’ community is in the use of the levels of team-role orientations in building the young scientists project teams and developing their social competence, which gives the opportunity to improve the education and training of young scientists. The possible directions of the research development are studying of the other approaches to team management, stress management and emotional well-being of young scientists. The possible ways of developing team work in particular and social competence in general in the process of education and training of young scientists are the implementation of special modules of soft skills development.